The influence of children on decision-makers in their homes : a case study in environmental education - Kruger, Jacqueline (Rhodes University, Faculty of Education, Department of Education, 1992)
This study explores the possible influence of twenty children on their 'parents', with a view to better understanding the potential 'multiplier effect' of children regarding environmental responsibility. The criteria employed to study the potential influence included certain of the environmental activities learnt by the children during an Environmental Education programme. The programme was undertaken by the researcher with a Std 4 class from Ryneveld PrimeÌ‚reskool in Graaff-Reinet. An action research approach was adopted and results were analysed qualitatively. Due to the short duration and exploratory nature of the project, these results should be viewed as tentative. Proposals are made for increasing the impact of Environmental Education programmes in peri-urban township communities, and recommendations are put forward to help facilitate related studies in the future.
Keywords: Environmental education -- South Africa; Parent and child -- South Africa